ИСПОЛЬЗОВАНИЕ ИСКУССТВЕННОГО ИНТЕЛЛЕКТА ПРИ ЯЗЫКОВОМ ПЕРЕВОДЕ («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article contains the relevance of using artificial intelligence in translation and teaching foreign languages. The relevance of this topic and the advantages of using AI are shown. The article also briefly highlights the work of linguists on this topic. It is highlighted exactly what aspects need to be paid attention to at the time of their expression on the database.Particular attention is paid to two aspects of lexicography, conditionally related to each other: scientific-theoretical and practical.It is shown how the use of artificial intelligence in machine translation opens up new opportunities for the development and improvement of language communication.
Keywords: development, artificial intelligence, fact, machine translation, linguistics, aspect, algorithm.